2017
DOI: 10.3390/en10040492
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Flow of Nanofluids in a Y-Type Intersection Channel with Multiple Pulsations: A Numerical Study

Abstract: Abstract:In this paper, we study pulsed flow and heat transfer in water-Al 2 O 3 nanofluids in a Y-type intersection channel with two inlets and one outlet. At the two inlets, two sinusoidal velocities with a phase difference of π are applied. We assume that the shear viscosity and the thermal conductivity of the nanofluids depend on the nanoparticles concentration. The motion of the nanoparticles is modeled by a convention-diffusion equation, where the effects of the Brownian motion, thermophoretic diffusion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…In current work, the non-homogenous single phase model will be used; this approach retains several important features of the two-fluid (two-phase) approach, with lower computational cost [36]. If the effects of electro-magnetism and chemical reactions are ignored, the governing equations, for a single component suspension, are the conservation equations for mass, linear and angular momentum, particle concentration, and energy [11,33,36,37].…”
Section: Governing Equationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In current work, the non-homogenous single phase model will be used; this approach retains several important features of the two-fluid (two-phase) approach, with lower computational cost [36]. If the effects of electro-magnetism and chemical reactions are ignored, the governing equations, for a single component suspension, are the conservation equations for mass, linear and angular momentum, particle concentration, and energy [11,33,36,37].…”
Section: Governing Equationsmentioning
confidence: 99%
“…/∂t + [grad(.)]v. The conservation of angular momentum indicates that in the absence of couple stresses the stress tensor is symmetric, that is, T = T T [36].…”
Section: Conservation Of Linear Momentummentioning
confidence: 99%
See 2 more Smart Citations
“…They demonstrated that there is an ideal incentive for nanofluid volume fraction to control heat exchange, temperature appropriation, and stream field. Wu et al [46] studied the heat transfer and pulsed flow in a Y-type crossing point channel with two inlets and one outlet utilizing water-Al 2 O 3 nanofluids. They demonstrated that the utilization of the pulsed flow enhances the Nusselt number, particularly for a huge Reynolds number and a high pulse frequency.…”
Section: Introductionmentioning
confidence: 99%